Desentralisasi dan Sistem Pengukuran Kinerja Pemerintah Daerah: Kajian Independen Terhadap Sistem Evaluasi Kemampuan Penyelenggaraan Otonomi Daerah (EKPOD) - Kartasasmita, Pius Suratman (Magister Administrasi Publik (MAP) FISIPOL Universitas Gadjah Mada, 2011)
Implementation of decentralization in Indonesia, as mandated by Law Number 32/2004, has three main objectives, which include improving the welfare of society, public services, and regional competitiveness. This study holds an assumption the that the importance of Local Government Performance System, both in order to reduce euphoria as well as to ensure the accomplishment of decentralization goals that set out by the law. The ministry of Home Affairs, has developed three local government performance measurement system as mandated by PP Number 6/2008, namely: the evaluation system of new autonomous regions (EDOB), the evaluation of local governance performance system (EKPPD), and the evaluation of regional autonomy capacity (EKPOD). This study assesses the framework and applicability of the EKPOD system. Using data from 17 Districts/ municipal governments, the researcher conclude that EKPOD data are limited. With respect to data availability, these are limited to 2004-2006 period, which is not long enaugh to use in assessing the EKPOD system which requires 5 years in succession. Of the required 175 data units, only 40-60% are available (70-105 data units). These findings and statistical factor analysis, suggest that the number of EKPOD indicators should be reduced to 19 with 25 data elements. This will not only enhance system applicability, but also reduce financial resources needed to establish he baseline data by 86 percent.